Risk Factors of Venous Thromboembolism in Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Zhang, Hua; Wang, Xuehong (Frontiers in Medicine, 2021)
Background: Patients suffering from chronic inflammatory disorders, such as inflammatory bowel disorder, are at higher risk of developing thromboembolism. The chronic inflammatory nature of inflammatory bowel disease has been identified as a predominant reason for a state of Virchow’s triad (i.e. endothelial dysfunction, stasis, and general hypercoagulability), eventually leading to the onset of venous thromboembolism. Recent studies show that certain factors, such as demographics, medication history, and history of surgical intervention may increase thromboembolism risk in patients with inflammatory bowel disease. However, to date, no study has attempted to evaluate the effect of different risk factors associated with the development of venous thromboembolism in inflammatory bowel disease patients. Objective: To evaluate the risk factors that can influence the incidence of venous thromboembolism in patients with inflammatory bowel disease. Methods: Academic literature was systematically searched based on the PRISMA guidelines across five databases: Web of Science, EMBASE, CENTRAL, Scopus, and MEDLINE. A random-effect meta-analysis was conducted to evaluate the hazard ratio for the risk factors (i.e. aging, gender, steroid therapy, surgery, and ulcerative colitis) that can influence the incidence of venous thromboembolism in patients with inflammatory bowel disease. Results: From a total of 963 studies, 18 eligible studies with 1062985 (44.59 ± 10.18 years) patients suffering from inflammatory bowel disease were included in the review. A meta-analysis revealed a higher risk of aging (Hazard’s ratio: 2.19), steroids (1.87), surgery (1.48), and ulcerative colitis (2.06) on venous thromboembolism in patients with inflammatory bowel disease. We also found that the female gender (0.92) did not increase the incidence of venous thromboembolism in inflammatory bowel disease patients. Conclusion: The study provides preliminary evidence regarding high risks associated with ulcerative colitis, steroid consumption, and aging for the development of venous thromboembolism in patients with inflammatory bowel disease. The findings from this study may contribute to developing awareness among clinicians, better risk stratification and prevention of venous thromboembolic complications in patients with inflammatory bowel disease.